Breaking habits: safety and efficacy of elective electrocardioversion of atrial fibrillation and atrial flutter in the setting of day hospital - Ammar Brkić; Minela Bećirović; Emir Bećirović; Tarik Brkić; Esad Brkić; Denis Mršić; Amir Bećirović; Amila Jašarević; Emir Softić; Alma Mujić Ibralić (Medicinski glasnik, 2023)
Aim: To examine safety and efficiency of electrocardioversion (EC) in elective treatment of atrial fibrillation and atrial flutter in the setting of Day Hospital by determining success rate, frequency of adverse events and possible cost benefit compared to admitting a patient into hospital. Methods: This prospective observational cohort study was performed in Day Hospital and in Intensive Care Department of Internal Medicine Clinic, University Clinical Centre Tuzla from January 2019 to December 2022 and included 98 patients with a persistent form of atrial fibrillation (AF) or atrial flutter. The patients who were divided in two groups, 56 hospitalized and 42 patients accessed in Day Hospital. In all patients, medical history, physical examination, electrocardiogram (ECG) and transthoracic echocardiogram (TTE) evaluation was performed in addition to laboratory findings. Electrocardioversion was performed with a monophasic General Electric defibrillator in anterolateral electrode position with up to three repetitive shocks. Results: In hospital setting group overall succes rate of electrocardioversion was 85%, with average 2.1 EC attemps, there was with one fatal outcome due to stroke, one case of ventricular fibrillation (VF) due to human error, and 6 minor adverse events; with average cost of was 1408.70 KM (720.23 €) per patient. In Day Hospital setting succes rate was 88%, with average 2 EC attempts, no major adverse events, 8 minor adverse events; and average cost was of 127.23 KM (65.05 €) per patient. Conclusion: Performing elective electrocardioversion in Day Hospital setting is as safe as admitting patients into hospital but substantially more cost effective.
Keywords: adverse events; cost benefit analysis; electrocardiography; intensive care unit